POSTERIOR ANEURYSMORRHAPHY & LATERALIZATION OF ANEURYSMAL FISTULA VEIN: A MODIFICATION OF EXISTING ANEURYSMECTOMY TECHNIQUES - Imtiaz, Nauman; Hafiz Khalid Pervaiz; Waqas Ahmed; Kishwar Ali; Fazal e Haider; Afzal Siddique; Rai Ahmed Khan Kharl; Palwasha Shahid (Journal of Ayub Medical College Abbottabad, 2021)
Background: To present a new modification of aneurysmectomy technique for the management of aneurysmal fistula vein. This cross-sectional study was carried out at Vascular Surgery department, Combined Military Hospital Rawalpindi from 1st October 2014 to 30th December 2018. Methods: This modified aneurysmectomy procedure was performed in 20 patients. Massive diffuse venous dilatation of vein, necrosis of overlying skin, reduction in the cannulation area and pain were the indications of surgery. Revision was performed by rotating the mobilized vein to 180°, excising redundant vein, reducing diameter, repairing venotomy posteriorly and placing the vein in a mobilized skin flap over the fascia of biceps muscle away from skin suture line, to facilitate subsequent cannulation and post puncture haemostasis. The rationale of this modification was to prevent damage to the usual anteriorly placed suture line during needle insertion for haemodialysis. The data were analysed by using SPSS version 25.0. Results: The mean age of patients was 45.45±14.75 years with a range of 12-65 years. Sixteen patients (80.0%) were having brachiocephalic fistula while 4 patients (20.0%) had radio cephalic fistula. The mean time of reuse of AVF after vein Aneurysmectomy was 24.55±5.3 days with half of the patients having reuse of AVF after 3 weeks. Three (15%) patients developed hematoma while 2(10%) patients developed skin necrosis. Fifteen (75%) patients had no surgery related complications after procedure. Conclusion: Posterior suturing and lateralization of aneurysmal vein under mobilized skin flap is a safe, effective and easy to learn modification of aneurysmectomy procedure for the management of aneurysmal dilatation of fistula vein.